STUDI SISTEM PROTEKSI RELE DIFERENSIAL PADA TRANSFORMATOR PT. PLN ( PERSERO ) KERAMASAN PALEMBANG - Subianto, Subianto (JURNAL SURYA ENERGY, 2016)
The distribution of electric energy in the system required reliability of the protection system on the equipment to get a better job to transmit electrical energy to consumers, one of which, namely the protected Transformer protection by Differential Rele. The transformer is a tool to convert electrical voltage and current values are different in magnetic, and the Differential is a Rele rele the principle it works on the basis of the balance (balance), which compares the Current Transformer (CT) secondary of currents is installed on the terminal-terminal equipment or electrical installation which is secured. Here be discussed how to work when the differential rele interference in the area of work of such disorders, Differential Rele is short circuit interruption 3 Phase Transformer primary side 150 kV with the ratio of CT 400/5A and the secondary side of the transformer 70 kV CT ratio 800/5A. Obtained results of calculation for short circuit 3 primary side 150 kV Phase is 1204.57 Ampere with a value of Differential Current setting rele 1.99 Ampere, stated that Differential Rele don't work because the current setting rele is larger than the current calculation of short circuit 3 phase occurs. 3 Phase short circuit interruption in the secondary side 70 kV is 4636.77 Ampere and Rele will work there due to the current which passes through the area of work with a current rating rele differential setting rele is smaller than the current value of the differential or the value of current that operates from 3 Phase short circuit interruption. Keywords: .Â